Risk Analysis and Mitigation Strategies in Overcoming Cyber Attacks in Information Technology Companies Using the OCTAVE Framework - Ikbal Danu Setiawan; Septi Andryana (Eduvest - Journal of Universal Studies, 2025)
In the increasingly advanced digital era, information technology companies are the main target of increasingly complex and intense cyberattacks. To address these threats, risk analysis is a crucial step to identify, evaluate, and mitigate risks associated with cyberattacks. This study aims to analyze the risk of cyber attacks on information technology companies using the Octave framework. The Octave framework provides systematic and structured risk management guidelines that can be applied to different types of risks, including cyber risks. Based on the results of the risk analysis, priority is given to risks with high severity to obtain appropriate mitigation measures. The proposed risk mitigation strategy includes the implementation of security technologies, the development of security policies and procedures, and the increase in employee awareness and training on cybersecurity practices. In addition, this study emphasizes the importance of continuous monitoring and periodic evaluation of the effectiveness of the mitigation strategies implemented. In an effort to combat cybercrime and protect digital security, this writing uses the Octave framework method. The results of this study show that by using the Octave framework, companies can effectively identify and manage the risk of cyberattacks. The implementation of this framework not only improves information security, but also provides a systematic and structured approach to cyber threats, thereby strengthening the company's resilience to future attacks.